Not all cementless stems are created equal: A selection algorithm - Schmalzried, Thomas P. (Seminars in arthroplasty, 2016)
Patients, and their femurs, come in all shapes, sizes, and types. Fortunately, so do cementless femoral stems. Each surgeon should have a “go to” cementless femoral component that can address over 90% of cases. A simple approach is to separately consider (A) the part inside the bone and (B) the part outside the bone. The inner-cortical geometry (Dorr type) and bone density influence stem size (the part inside the bone) and influence femoral canal preparation. Femoral deformity or old hardware can occasionally necessitate the use of a short stem or a modular stem. Restoration of limb length and offset is a function of the neck angle and length (the part outside the bone). Undersizing of cementless stems increases the risk of aseptic loosening while restoration of limb length and offset favorably affects patient satisfaction and function.